A Method to Assess the Potential for and Consequences of Energy Retrofits in Swedish Historic Buildings. (July 2014) - Broström, Tor; Eriksson, Petra; Liu, Linn; Rohdin, Patrik; Ståhl, Fredrik; Moshfegh, Bahram
<x content-type="archive" xml:space="preserve">Abstract</x> The Swedish research project 'Potential and Policies for Energy Efficiency in Swedish Historic Buildings' aims to investigate the interdependency between political energy targets and effects on the built heritage. The first part of this paper presents an iterative and interactive method to assess the potential for and consequences of improving the energy performance in a stock of historic buildings. Key elements in the method are: categorisation of the building stock, identifying targets, assessment of measures, and life-cycle cost optimisation. In the second part of the paper, the method is applied to a typical Swedish building. The selected case study shows how the method allows for an interaction between the quantitative assessment of the techno-economic optimisation and the qualitative assessment of vulnerability and other risks. Through a multidisciplinary dialogue and iteration it is possible to arrive at a solution that best balances energy conservation and building conservation in a given decision context.